What does women's empowerment have to do with malnutrition in Sub-Saharan Africa? Evidence from demographic and health surveys from 30 countries - Sanni Yaya; Emmanuel Kolawole Odusina; Olalekan A. Uthman; Ghose Bishwajit (BMC, 2020)
Abstract Background The reduction of childhood malnutrition has been identified as a priority for health and development in sub Saharan African countries. The association between women's empowerment and children's nutritional status is of policy interest due to its effect on human development, labour supply, productivity, economic growth and development. This study aimed to determine the association between women's empowerment and childhood nutritional status in sub Saharan African countries. Methods The study utilized secondary datasets of women in their child bearing age (15-49 years) from the latest Demographic and Health Survey (DHS) conducted in 2011-2017 across 30 sub Saharan Africa countries. The outcome variable of the study was childhood nutritional status while the exposure variable was women's empowerment indicators such as decision making and attitude towards violence. Analyses were performed at bivariate level with the use of chi square to determine association between outcome and exposure variables and at multivariate level with the use of regression models to examine the effect of women's empowerment on childhood nutritional status. Results Women's socio-demographic and other selected characteristics were statistically significantly associated with childhood nutritional status (stunted and underweight) at p < 0.001. These characteristics were also statistically significantly associated with empowerment status of women (Decision-making, Violence attitudes and Experience of violence) at p < 0.001 except for child age and sex. The association between childhood nutritional statuses and women's empowerment (all three empowerment measures) was significant after controlling for other covariates that could also influence childhood nutrition statuses at p < 001. Two of the empowerment measures (attitudes towards violence and experience of violence) showed positive association with childhood nutritional statuses while the third (decision-making) showed negative association. Conclusion There is an independent relationship between childhood nutrition status and women's empowerment in sub Saharan African countries. Women's empowerment was found to be related to childhood nutritional status. Policies and programmes aiming at reducing childhood malnutrition should include interventions designed to empower women in Sub-Saharan Africa.